Kelengkapan Pengisian Surat Keterangan Kematian Pasien Rawat Inap Rumah Sakit X - Yuliana Pratiwi; Andi Suhenda; Fery Fadly; Ayu Rahayu Lestari (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2025)
Incorrect completion of death certificates can hinder the identification of causes of death and affect the accuracy of mortality data. This study aims to evaluate the completeness of death certificates for inpatients at Hospital X in 2023. The study used a quantitative approach with descriptive methods and total sampling techniques. The study population consisted of all SKKs for inpatients in 2023. Data were collected through a process of collecting, editing, tabulating, and presenting. The results showed that the highest completeness was found in the items of the name of the person filling out the form and the day/date of death at 100%, while the lowest completeness was found in the items of occupation at 42% and gender at 75%. This incompleteness was due to the low awareness of doctors in filling out the SKK. In conclusion, although some items were completely filled out, several items were found to be incomplete and needed improvement. Hospitals are advised to create and consistently implement quantitative analysis SOPs and increase the awareness of medical personnel regarding the importance of completing the SKK to support the accuracy of death reporting and health policy decision-making Pengisian Surat Keterangan Kematian (SKK) yang tidak sesuai standar dapat menghambat identifikasi penyebab kematian dan berdampak pada ketepatan data mortalitas. Penelitian ini bertujuan untuk mengevaluasi kelengkapan pengisian SKK pasien rawat inap di Rumah Sakit X tahun 2023. Penelitian menggunakan pendekatan kuantitatif dengan metode deskriptif dan teknik total sampling. Populasi penelitian adalah seluruh SKK pasien rawat inap tahun 2023. Data dikumpulkan melalui proses collecting, editing, tabulating, dan penyajian. Hasil penelitian menunjukkan bahwa kelengkapan tertinggi terdapat pada item nama pengisi serta hari/tanggal meninggal sebesar 100%, sementara kelengkapan terendah ditemukan pada item pekerjaan 42% dan jenis kelamin 75%. Ketidak lengkapan ini disebabkan oleh rendahnya kesadaran dokter dalam pengisian SKK. Kesimpulannya, meskipun terdapat item yang telah terisi lengkap, masih ditemukan beberapa item yang kurang lengkap sehingga perlu perbaikan. Rumah sakit disarankan untuk membuat dan menerapkan SOP analisis kuantitatif secara konsisten serta meningkatkan kesadaran petugas medis terhadap pentingnya kelengkapan pengisian SKK guna mendukung akurasi pelaporan kematian dan pengambilan keputusan kebijakan kesehatan